EFFECTIVENESS OF THE WORLD TRADE ORGANIZATION IN REGULATING INTERNATIONAL TRADE (International Journal of Food and Nutritional Sciences, 2022)
This study evaluates the Effectiveness of the World Trade Organization in Regulating International Trade. World Trade Organization (WTO) in regulating international trade is a multifaceted issue encompassing trade liberalization, dispute resolution, monitoring and surveillance, and development assistance. Established in 1995, the WTO has played a crucial role in promoting global trade by negotiating and implementing agreements that reduce tariffs and other trade barriers, thus facilitating smoother and more predictable trade flows. Its dispute resolution mechanism is a cornerstone of its effectiveness, providing a formal process for resolving trade conflicts and ensuring adherence to trade rules. This system has generally succeeded in maintaining stability in international trade relations. The WTO also performs essential monitoring and surveillance functions through its Trade Policy Review Mechanism (TPRM), which reviews and assesses member countries' trade policies to ensure transparency and compliance with WTO agreements. This helps identify potential issues and fosters a rules-based trading environment. Additionally, the WTO supports developing countries through technical assistance and capacity-building programs, aiming to enhance their ability to participate in global trade and benefit from its opportunities.However, the WTO faces significant challenges and criticisms. These include concerns about the disproportionate benefits to wealthier nations, difficulties in reaching consensus on major trade negotiations, and debates over national sovereignty. The organization’s ability to adapt to emerging trade issues, such as digital trade and environmental concerns, is also under scrutiny. Overall, while the WTO has made substantial contributions to global trade regulation and stability, its effectiveness is continually tested by evolving global trade dynamics and the need for reform to address new and existing challenges.